2014
DOI: 10.1021/jm501095r
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nucleus DNA with a Cyclometalated Dipyridophenazineruthenium(II) Complex

Abstract: Recently, coordinatively saturated and substitutionally inert Ru(II) complexes have been investigated as anticancer agents. Herein a cyclometalated Ru(II) complex, [Ru(bpy)(phpy)(dppz)](+), was found to be rapidly taken up by cancer cells, and nearly 90% of the complex accumulated in the nuclei of cancer cells after a 2 h incubation. The anticancer activity of this complex was screened against a panel of cancer cell lines. Remarkably, it exhibited IC50 values that were an order of magnitude lower than those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(130 citation statements)
references
References 88 publications
(120 reference statements)
4
126
0
Order By: Relevance
“…Interestingly, the Ru(II) complexes 13s to 13x had lower IC 50 values against HeLa cells, resulting from an increase of the volume of the chelating ligands, which is partly due to the larger chelating ligands which produces higher cellular uptake and stronger interactions with DNA. 80,229,231 Recently, the same group also designed some cycloruthenated compounds with significant potency in hypoxic and cisplatin-resistant cancer cell lines. 232,233 Complex 13y - 5 (see Fig.…”
Section: Ruthenium(ii) Polypyridyl Complexesmentioning
confidence: 99%
“…Interestingly, the Ru(II) complexes 13s to 13x had lower IC 50 values against HeLa cells, resulting from an increase of the volume of the chelating ligands, which is partly due to the larger chelating ligands which produces higher cellular uptake and stronger interactions with DNA. 80,229,231 Recently, the same group also designed some cycloruthenated compounds with significant potency in hypoxic and cisplatin-resistant cancer cell lines. 232,233 Complex 13y - 5 (see Fig.…”
Section: Ruthenium(ii) Polypyridyl Complexesmentioning
confidence: 99%
“…[50][51][52][53] Recently, Ru(II) cyclometalated complexes have been also investigated as anticancer agents. [54][55][56][57] However, this topic together with the Ru(II) polypyridyl complexes activated by light or the non-coordinatively saturated Ru(II) polypyridyl complexes are not reviewed here. We send the interested readers to an excellent, very recent Review of Zeng and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…11-16) Pfeffer and colleagues 17,18) and Chao and colleagues 19,20) have found that some cyclometalated ruthenium(II) complexes are good candidates for becoming anticancer drugs. A cyclometalated ruthenium fragment with a metal-carbon σ bond is a crucial element for a potential anticancer drug.…”
Section: )mentioning
confidence: 99%
“…[5][6][7][8][9][10] Several ruthenium complexes that display an activity comparable to that of cisplatin have been described, and in some cases activities are even better. [11][12][13][14][15][16] Pfeffer and colleagues 17,18) and Chao and colleagues 19,20) have found that some cyclometalated ruthenium(II) complexes are good candidates for becoming anticancer drugs. A cyclometalated ruthenium fragment with a metal-carbon σ bond is a crucial element for a potential anticancer drug.…”
mentioning
confidence: 99%